Plastic gear loss estimates from remote observation of industrial fishing activity. Issue 1 (30th July 2021) - Kuczenski, Brandon; Vargas Poulsen, Camila; Gilman, Eric L.; Musyl, Michael; Geyer, Roland; Wilson, Jono
Abstract: Derelict fishing gear is a highly visible source of marine plastic pollution, causing mortality and ecosystem degradation with uncertain long‐term consequences. The quantity of derelict gear entering the oceans remains unknown because of heterogeneity in fishing gear and effort, as well as inadequate monitoring. Prior studies have been limited in scope to specific fisheries and regions, and large‐scale estimates lack an empirical basis. It is critically important for decision makers to have credible information in order to design effective remediation efforts. We estimated the amount of industrial fishing effort and the associated plastic debris entering the ocean globally each year from lost fishing gear. Using remote observations of fishing vessel activity paired with technical fishing gear models, we generated a bounding estimate for gear operation and loss worldwide in 2018. We estimate that industrial trawl, purse‐seine and pelagic longline fisheries operated 2.1 Mt of plastic gear over 2018 to obtain 49.7 Mt of retained and discarded catch, representing 74% of industrial marine capture globally. The median estimate for plastic gear lost during the use of these gear types was 48.4 kt (95% confidence interval: 28.4–99.5 kt). This estimate excludes abandoned and discarded gear. Improved observation, especially of small‐scale fisheries, is needed to better understand the sources of derelict gear. These findings serve as a benchmark for future monitoring and management efforts to reduce derelict gear in the global ocean.